2005
DOI: 10.1016/j.otohns.2005.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Eustachian Tube Dysfunction in Allergic Rhinitis

Abstract: Allergic rhinitis patients have a higher risk of eustachian tube dysfunction, particularly during childhood. Tympanometry is a noninvasive, readily available procedure that may be useful in these patients to prevent chronic middle-ear disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
3
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 20 publications
4
71
3
5
Order By: Relevance
“…It is therefore not surprising that allergic inflammation with concomitant mucosal swelling may impair the function of the Eustachian tube. Allergic rhinitis patients have a higher risk of Eustachian tube dysfunction assessed by tympanometry than nonallergic subjects, particularly during childhood (2129).…”
Section: Tubal Dysfunctionmentioning
confidence: 99%
“…It is therefore not surprising that allergic inflammation with concomitant mucosal swelling may impair the function of the Eustachian tube. Allergic rhinitis patients have a higher risk of Eustachian tube dysfunction assessed by tympanometry than nonallergic subjects, particularly during childhood (2129).…”
Section: Tubal Dysfunctionmentioning
confidence: 99%
“…6,7 Nasal septal deviation has also been associated with symptoms of ETD; this is based on some studies which suggested that, in patients who were unable to equalise pressure during scuba training or submarine service, submucous resection of the nasal septum resolved apparent ETD symptoms. [8][9][10][11] Dysfunction of the Eustachian tube may also be related to failure of the muscles associated with Eustachian tube opening.…”
Section: Aetiology and Prevalencementioning
confidence: 99%
“…In 2005, considering the impact of chronic middle ear disease regardless of age, Lazo-Saenz et al [55] conducted a study to assess eustachian tube function using tympanometry in individuals with AR and to compare them with healthy individuals with the aim of exploring the magnitude of OM diseases in an at-risk population such as those with allergies. The tympanometric measurements indicated that children and adults with AR had more negative values of tympanometric peak pressure (TPP) than controls (P≤0.05), but the main finding of tympanometry resulted among the children with AR who were younger than 11 years of age.…”
Section: Tympanometric Measurementsmentioning
confidence: 99%
“…The tympanometric measurements indicated that children and adults with AR had more negative values of tympanometric peak pressure (TPP) than controls (P≤0.05), but the main finding of tympanometry resulted among the children with AR who were younger than 11 years of age. In fact, it was shown that negative values of TPP and abnormal curves were present in 15.5% of children (13% C curves, 3% B curves), while only A curves were found in the control group (P=0.03) [55]. Also, Yeo et al [45] investigated the role of atopy in the development of OME and its effect on eustachian tube function after nasal provocation tests by tympanometric measurements.…”
Section: Tympanometric Measurementsmentioning
confidence: 99%